Factors Influencing Students' Interest in Utilising Qris Electronic Money - Manuputty, Gino G.; Pattinama, Gwenn L.L.; Hiariej, Nicoline (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The urgency of this research is to provide an understanding of the importance of using electronic money, in this case the Quick Response Indonesian Standard (QRIS) as part of implementing the industrial revolution 4.0 and can provide ease of payment in the academic process and reduce the risk of financial abuse. The aim of this research is to analyze the influence of perceived benefits, perceived ease of use and perceived risks on interest in using QRIS electronic money. This research was conducted on students at the Indonesian Christian University of Maluku (UKIM) located in the city of Ambon. The population in this study were all UKIM Ambon students at existing faculties, while the sample was determined using a purposive sampling technique using the Slovin formula. In data processing we will use data quality tests and classical assumptions before analyzing with multiple linear regression. The results of this study show that the variables perceived ease of use and perceived risk have a significant influence, while perceived usefulness shows an insignificant influence.